Pengaruh Material Absorber Terhadap Temperatur Keluaran Kolektor Surya - Ahmad Syuhada; Muhammad Ilham Maulana; Abraar Shalahuddin (Jurnal Teknik Mesin Unsyiah, 2018)
The function of solar collector is to increase the air that consist of absorber, air duct and glass cover. One of the factors that affect the collector output temperature increased is depend on high temperature absorber. An absorber serves to absorb heat from the sun, and heats flowing air in the air duct above the absorber. The heating of the air pass/route is greatly influenced by the flow patterns inside the collector. In this study the authors examined the use of variations absorber on solar collector. There were four variations of The absorber; iron sand, gram iron sand, asphalt hotmix, and iron sand asphalt. The research method is intended to determine the value of heat transfer by radiation, conduction and convection. Dimension of solar collector was used 300 cm x 80 cm. The best variation of absorber was gram iron sand type at the most optimum intensity of sun at 12 a.m-2 p.m.